Perceval : the story of the grail - Chrétien, de Troyes, active 12th century (Yale University Press, 1999)
One of the most influential storytellers in Western literature, French poet Chrétien de Troyes helped to shape the ever-fascinating legend of King Arthur and the Round Table. Of Chrétien's five surviving romantic Arthurian poems, the last and longest is Perceval, an unfinished work that introduces the story of the Grail-a legend quickly adopted by other medieval writers and taken up by a continuing succession of authors. In Chrétien's romance, Perceval progresses from a naive boyhood in rural seclusion to a position of high respect as a knight at Arthur's court. With the help of two teachers-his mother and Gornemant of Goort-Perceval is ultimately able to reject the worldly adventures chosen by other knights and seek important moral and spiritual answers.Acclaimed for his sensitive and faithful translations of the poems of Chrétien, Burton Raffel completes the Arthurian series with this rendition of Perceval. Raffel conveys to the modern English language reader all the delights of Chrétien's inventive storytelling, perceptive characterizations and vividly evoked emotions.